Liangzhu culture : society, belief and art in Neolithic China - Liu, Bin, 1961-; Qin, Ling, 1975-; Zhuang, Yijie (Abingdon, Oxon ; New York, NY : Routledge, 2018)
"Liangzhu culture (5,300-4,300 cal B.P.) represented the peak of prehistoric cultural and social development in the Yangtze Delta. Its centre is located near nowadays Hangzhou city and is considered one of the earliest urban centres in prehistoric China, called by archaeologists the Liangzhu Site Complex. Although it remains a mystery for many in the west, Liangzhu is well known in China for its fine jade crafting industry; its enormous, well-structured earthen compound and recently discovered hydraulic system; and its far-flung impact on contemporary and succeeding cultures. With six chapters contributed by frontline archaeologists, Liangzhu Culture contextualises Liangzhu in broad socioeconomic and cultural backgrounds and provides new, first-hand data to help explain the development and structure of this early urban centre. Among its many insights, the volume reveals how elites used jade as a means of acquiring social power, and how Liangzhu and its centre stand in comparison to other prehistoric urban centres in the world. This book, the first of its kind published in English language, will be a useful guide to students at all levels interested in material cultures and social structures in prehistoric China and beyond"--
Situating the Liangzhu culture in late Neolithic China: an introduction -- The Liangzhu City: new discoveries and research -- Power and belief: reading the Liangzhu jade and society -- A controlled fine craft: jade production techniques in the Liangzhu Culture -- From the 'Songze Style' to the 'Liangzhu Mode' -- Shamanistic, historic and virtuous jade: continuity and change in early Chinese jade traditions.
OCLC-licensed vendor bibliographic record.
Keywords: Liangzhu culture; Jade art objects -- China -- Yangtze River Delta -- History; Social archaeology -- China -- Yangtze River Delta; Urban archaeology -- China -- Yangtze River Delta; Yangtze River Delta (China) -- Antiquities; Hangzhou Shi (China) -- Antiquities; SOCIAL SCIENCE / Archaeology